The Antimicrobial Peptide LL-37 Inhibits HIV-1 Replication - Peter Bergman; Lilian Walter-Jallow; Kristina Broliden; Birgitta Agerberth; Johan Soderlund (Current HIV Research, 2007)
The antimicrobial peptide LL-37 is the only cathelicidin that has been described in humans. LL-37 exerts chemotactic, immunomodulatory and angiogenic effects; activities that are mediated through binding to the formyl peptide receptor like (FPRL)-1 receptor. Agonistic ligation of FPRL-1 can also induce down-regulation of HIV-1 chemokine receptors and reduce susceptibility to HIV-1 infection in vitro. Therefore, we have evaluated the capacity of LL-37 to inhibit HIV-1 infection in vitro. Here we demonstrate that LL-37 inhibits HIV-1 replication in PBMC, including primary CD4+ T cells. This inhibition was readily reproduced using various HIV-1 isolates without detectable changes in the target cell expression of HIV-1 chemokine receptors. Accordingly, the HIV-1 inhibitory effect was shown to be independent of FPRL-1 signalling. Given the epithelial expression of LL-37, it may contribute to the local protection against HIV-1 infection.
Keywords: cathelicidin